Implementation of Conceptual Change Model - Computational Thinking (CCM-CT) to Increase Students’ Conceptual Understanding in Pascal’s Law - Dwi Anfusiyah; Achmad Samsudin; Agus Danawan (Universitas Lambung Mangkurat, 2024)
This research aimed to implement the Conceptual Change Model - Computational Thinking (CCM-CT) in enhancing students’ conceptual understanding of Pascal’s Law. This research used a quasi-experimental design with a pretest-posttest control-group design. The population for this research comprised all second-semester grade XI MIPA students in a public high school in Bandung City. The sampling method used was purposive sampling, specifically selecting students who had not previously studied Pascal's Law material. The sample included two classes: the experimental class, which received treatment through CCM-CT learning, and the control class, which underwent treatment using CCM learning. The experimental class consisted of 8 male students and 28 female students, while the control class consisted of 9 male students and 27 female students aged 15-17 years. The data collection technique for students’ conceptual understanding used a Four-tier test instrument on Pascal’s Law. The data analysis technique used the N-Gain test to assess the enhancement of students' conceptual understanding through activities to alter their conceptions during the learning process. The results revealed a distinction in conceptual understanding between students who utilized CCM-CT learning and those who employed CCM learning. The N-Gain pre-test and post-test values in the experimental class, which implemented CCM-CT learning, were 0.71, interpreted as